RESUMPTION AND LAST RESORT - Aoun, Joseph (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2018)
This paper discusses the derivation of definite and indefinite relative clauses in Lebanese Arabic. The two types of relative clause are similar in that they require resumptive pronouns and do not exhibit island effects. Based on reconstruction effects, I however argue that definite relatives may be either base-generated or derived by movement, whereas indefinite relatives can only be base-generated.